2021
DOI: 10.2174/1568026621666210521142131
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Bioenergetic and Metabolic Changes in Patients with Autism Spectrum Disorder

Abstract: Background: Although Autism Spectrum Disorder (ASD) is considered a heterogeneous neurological disease in childhood, a growing body of evidence associates it with mitochondrial dysfunction explaining the observed comorbidities. Introduction: The aim of this study is to identify variations in cellular bioenergetics and metabolism dependent on mitochondrial function in ASD patients and healthy controls using peripheral blood mononuclear cells (PBMCs). We hypothesized that PBMCs may reveal the cellular patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In agreement with the former findings, higher respiratory capacities and complex IV activity were reported in a lymphoblastoid cell line derived from an autistic child (Hassan et al 2021). Finally, peripheral blood mononuclear cells indicate that patients with ASD have increased respiratory reserve capacity and maximal respiration (Gevezova et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the former findings, higher respiratory capacities and complex IV activity were reported in a lymphoblastoid cell line derived from an autistic child (Hassan et al 2021). Finally, peripheral blood mononuclear cells indicate that patients with ASD have increased respiratory reserve capacity and maximal respiration (Gevezova et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This information further validates the hypothesis that the development of ASD may be associated with exposure to As. As may affect cellular metabolic processes, ASD was once described as a metabolic disorder characterised by alterations in the metabolism of glucose, amino acids and lipids ( Gevezova et al, 2021 ; Du et al, 2022 ). On the other hand, some studies reported no significant association between exposure to As via measurement in hair samples and the development of ASD in children ( De Palma et al., 2012 ; Fido & Al-Saad, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis of testing sources showed that compared with the healthy controls, ASD children had higher arsenic concentrations in their hair, urine, and blood ( P < 0.05), which further validated the hypothesis that arsenic exposure might be associated with the occurrence of ASD. ASD was once considered to be a metabolic disease, characterized by a metabolic disorder of glucose, lipid, and amino acid ( 84 , 85 ). Arsenic could affect the cellular metabolic processes ( 86 ).…”
Section: Discussionmentioning
confidence: 99%